Closed loop control of voltage source converters during faults in high voltage DC transmission system. Issue 2 (April 2021) - Ramesh, P; Kirubakaran, D; Suresh, A; Rashmi, MR
High voltage DC transmission is very cost effective alternate solution for high voltage AC transmission. High voltage DC transmission towers occupy less space and poles carry more current compared to high voltage AC system. High voltage DC transmission lines are emerging as an alternate solution for flexible AC transmissions (FACTS) technology. Earlier either thyristor valves or mercury valves were used in converters. Voltage source converter has replaced conventional converter in high voltage DC system because of their flexible control, black start capability, and they can work with weak AC system. Switching at higher frequency is also an added advantage. In voltage source converter-based high voltage DC transmission, both real and reactive power transmitted can be controlled whereas in conventional line commutated converter-based high voltage DC transmission system, only the real power transmitted was controlled. There may be chances of grid faults in sending end and receiving end stations. The typical faults are single line fault, double line to ground fault and three phase fault. The faults in one high voltage DC station should not affect the other end station. Necessary control should be initiated to take care of AC faults on both the sides that are before rectification in the sending end station and after inversion in the receiving end station. To handle such faults, the voltage source converters should be controlled to regulate the power transmitted through the line in such a way that the fault in one grid will not affect the parameters of the other grid. This paper presents closed loop control of both voltage source converters to take care of line to ground fault. The controller uses PQ theory. The behavior of high voltage DC system during fault without and with controller is presented in this paper. This simulation study is used to educate electrical transmission and faults detection to the trainees, they can easily understand.